2014
DOI: 10.1002/aenm.201400519
|View full text |Cite
|
Sign up to set email alerts
|

A Scalable Nanogenerator Based on Self‐Poled Piezoelectric Polymer Nanowires with High Energy Conversion Efficiency

Abstract: nanowires, [ 7 ] PbZr x Ti 1-x O 3 nanowires [ 8 ] and nanoribbons [ 9,10 ] and poly(vinylidene fl uoride) (PVDF) nanofi bers [ 11 ] have all revealed promising energy harvesting performance. There has since been an ongoing concerted effort in developing this relatively new research fi eld, connecting nanotechnology with the fi eld of energy. [ 12 ] Piezoelectric nanowires are particularly attractive for energy harvesting due to their robust mechanical properties and high sensitivity to typically small ambient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
169
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(173 citation statements)
references
References 40 publications
3
169
1
Order By: Relevance
“…Even then, it has been reported that electrically poled P(VDF-TrFE) nanowire arrays could have over 10 times higher piezoelectric coefficients than normal P(VDF-TrFE) thin films undergoing the same treatment [25]. More recently, nanowire synthesis approaches making use of a nanoconfinement growth effect have been found to be more likely to result in so-called 'selfpoled' β phase NWs [21,26], mostly observed, for example, in template-assisted growth whereby polymer NWs are grown within nanoporous templates by infiltration from solution or melt, and where the resulting NWs do not require external electrical poling in order to exhibit piezoelectric behaviour. Self-poling results from some degree of molecular alignment of the polymer chains along the length of the nanowire, which may arise as a result of the high degree of shear force experienced by the polymer solution during capillary infiltration.…”
Section: Piezoelectric Polymersmentioning
confidence: 99%
See 3 more Smart Citations
“…Even then, it has been reported that electrically poled P(VDF-TrFE) nanowire arrays could have over 10 times higher piezoelectric coefficients than normal P(VDF-TrFE) thin films undergoing the same treatment [25]. More recently, nanowire synthesis approaches making use of a nanoconfinement growth effect have been found to be more likely to result in so-called 'selfpoled' β phase NWs [21,26], mostly observed, for example, in template-assisted growth whereby polymer NWs are grown within nanoporous templates by infiltration from solution or melt, and where the resulting NWs do not require external electrical poling in order to exhibit piezoelectric behaviour. Self-poling results from some degree of molecular alignment of the polymer chains along the length of the nanowire, which may arise as a result of the high degree of shear force experienced by the polymer solution during capillary infiltration.…”
Section: Piezoelectric Polymersmentioning
confidence: 99%
“…In general, typical thin film fabrication often results in α phase PVDF (shown in figure 1(a)) which does not behave exhibit piezoelectricity due to net cancellation of dipoles along the chain [16]. Poling with either mechanical stretching, electric field or from controlled growth may force the polymer into a ferroelectric polar β phase which exhibits the strongest piezoelectricity [20][21][22][23][24]. Co-polymers of PVDF where some of the hydrogen atoms are replaced with fluorine atoms are more likely to crystallise in a polar phase due to steric factors.…”
Section: Piezoelectric Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…20 In addition, the low output voltage could be accumulated and converted to a high voltage through the circuitry for a static energy harvester. 21,22 In summary, this is the first example of a rigid-flexible TEG based on the organic and inorganic hybrid TE legs with high output performance. It can generate more than 160 nW under a ∆T of 10 K and is flexible enough to apply it on the human wrist, taking advantage of the flexibility of PP-PEDOT thin film.…”
mentioning
confidence: 99%